2021
DOI: 10.3390/polym13162706
|View full text |Cite
|
Sign up to set email alerts
|

Fluoropolymer/Glycidyl Azide Polymer (GAP) Block Copolyurethane as New Energetic Binders: Synthesis, Mechanical Properties, and Thermal Performance

Abstract: In order to enhance the application performance of glycidyl azide polymer (GAP) in solid propellant, an energetic copolyurethane binder, (poly[3,3-bis(2,2,2-trifluoro-ethoxymethyl)oxetane] glycol-block-glycidylazide polymer (PBFMO-b-GAP) was synthesized using poly[3,3-bis(2,2,2-trifluoro-ethoxymethyl)oxetane] glycol (PBFMO), which was prepared from cationic polymerization with GAP as the raw material and toluene diisocyanate (TDI) as the coupling agent via a prepolymer process. The molecular structure of copol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…However, they are thermoset‐polymers that are often difficult to recycle. Furthermore, owing to the strong polarity of azide groups and the relatively inflexible nature of the polymer chain, they display both marked sensitivity and compromised mechanical characteristics 20–22 . To overcome these drawbacks and improve its performance, various azido‐based copolymers have been developed as binder for CSPs.…”
Section: Nitrogen‐rich Based Copolymer Bindersmentioning
confidence: 99%
“…However, they are thermoset‐polymers that are often difficult to recycle. Furthermore, owing to the strong polarity of azide groups and the relatively inflexible nature of the polymer chain, they display both marked sensitivity and compromised mechanical characteristics 20–22 . To overcome these drawbacks and improve its performance, various azido‐based copolymers have been developed as binder for CSPs.…”
Section: Nitrogen‐rich Based Copolymer Bindersmentioning
confidence: 99%
“…Xu et al [ 64 ] reported an alternate type of GAP-based fluorinated polyurethane, synthesized by the copolymerization of GAP and 3,3-bis(2,2,2-trifluoroethoxymethyl) oxetane] glycol (BFMO) using toluene diisocyanate (TDI) as the crosslinker ( Scheme 4 ).…”
Section: Reactive Structures Based On Fluoropolymer-based Bindersmentioning
confidence: 99%
“…Xu and coworkers [17] reported the synthesis of the fluorinated glycidyl azide polymer poly (2, 2, 2‐trifluoro‐ethoxymethyl epoxy‐ r ‐glycidyl azide), and the cook‐off test results indicated that the poly (TFEE‐ r ‐GA)/Al mixture gave a larger reaction energy than GAP/Al mixture. In another report from the same group, the fluorine‐containing polyurethanes of poly [3, 3‐bis (2, 2, 2‐trifluoro‐ethoxymethyl) oxetane] glycol‐block‐glycidyl azide polymer were synthesized, and the cook‐off test results also indicated that the PBFMO‐ b ‐GAP could enhance the energy release of the PBFMO‐ b ‐GAP/Al composites [18]. However, up to date, there have been very limited examples of energetic fluorine‐containing polymers, let alone a comprehensive understanding of their effect on the resultant energetic composites, including their basic properties, energy level and combustion, and so on.…”
Section: Introductionmentioning
confidence: 99%